PERANCANGAN SISTEM SELEKSI ATLET BOLAVOLI MENGGUNAKAN METODE SAW PADA SEKOLAH BOLAVOLI KUSUMA BHIRAWA - Taufiq Abidin; Yovi Litanianda; Andy Triyanto (KOMPUTEK, 2021)
The basic technique of volleyball itself is one of the most important elements in the game of volleyball, without mastering good basic techniques, the game cannot be played perfectly, the basic techniques of volleyball include serving, passing, smash and block (dam). Based on an interview with Coach at SBV, Kusuma Bhirawa who coaches players at the age of U-18 teenagers, explained that the selection of athletes in participating in the event is carried out according to the coach's feelings during training. After making direct observations at the Kusuma Bhirawa volleyball school with the existing problems, a decision support system will be built for the selection of volleyball athletes using the SAW method. SAW (Simple Additive Weighting) is a method in a decision support system with a weighted summation of the performance ratings of each alternative on all attributes. The alternative that has the highest value is the best alternative proposed. The criteria needed by the SbV trainer Kusuma Bhirawa in anthropometric measurements are height, physical fitness test criteria consisting of 60 m running, 60 sec pull ups, 60 sec sit ups, vertical jump, 1200 m run. volleyball smash technique criteria, passing over, passing down, serving and blocking. From the results of the correlation test that has been tried to get the correlation of the recommendation of the core player list from the application system compared to the player list from the coach with a value of 83.3%. Therefore, these results show that the SAW method has a fairly good correlation when used to determine the selection of volleyball athletes